2021
DOI: 10.1177/0306624x211065588
|View full text |Cite
|
Sign up to set email alerts
|

A Deeper Understanding of Child to Parent Violence (CPV): Personal Traits, Family Context, and Parenting

Abstract: The increase in the rate of child to parent violence is a concern for society in various countries. Different psychological and personal characteristics tend to define the profile of the minors who commit this type of offense. Various social factors have been also related to this type of violence, including exposure to violence, the family environment and parenting. The relationship between child to parent violence and previous exposure to violence has yet to be clarified. Comparatively little research on this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 96 publications
0
6
0
Order By: Relevance
“…In CPV, exposure to violence in the family context (including both direct and vicarious victimization) is a significant predictor of this type of violence (Gallego et al, 2019). Specifically, empirical studies with judicial populations point out that adolescents who attack their parents present higher levels of exposure to violence at home compared to other young offenders (Contreras & Cano-Lozano, 2016;Cuervo, 2021;Hernández et al, 2020). The relationship between CPV and exposure to violence at home has also been consistently observed in studies with community populations (e.g., Beckmann, 2020;Calvete, Orue, et al, 2015;Margolin & Baucom, 2014;Navas-Martínez & Cano-Lozano, 2022a;Simmons et al, 2020), finding, in addition, that direct victimization has a greater predictive capacity for CPV than vicarious victimization (e.g., Beckmann, 2020;Margolin & Baucom, 2014;Navas-Martínez & Cano-Lozano, 2022a).…”
Section: Research On Individual Family and Social Variables In Cpv Of...mentioning
confidence: 99%
See 1 more Smart Citation
“…In CPV, exposure to violence in the family context (including both direct and vicarious victimization) is a significant predictor of this type of violence (Gallego et al, 2019). Specifically, empirical studies with judicial populations point out that adolescents who attack their parents present higher levels of exposure to violence at home compared to other young offenders (Contreras & Cano-Lozano, 2016;Cuervo, 2021;Hernández et al, 2020). The relationship between CPV and exposure to violence at home has also been consistently observed in studies with community populations (e.g., Beckmann, 2020;Calvete, Orue, et al, 2015;Margolin & Baucom, 2014;Navas-Martínez & Cano-Lozano, 2022a;Simmons et al, 2020), finding, in addition, that direct victimization has a greater predictive capacity for CPV than vicarious victimization (e.g., Beckmann, 2020;Margolin & Baucom, 2014;Navas-Martínez & Cano-Lozano, 2022a).…”
Section: Research On Individual Family and Social Variables In Cpv Of...mentioning
confidence: 99%
“…One of the variables that has received greater empirical support in the scientific literature about CPV is exposure to violence at home (e.g., Beckmann, 2020;Contreras & Cano-Lozano, 2016;Cuervo et al, 2021;Hernández et al, 2020;Navas-Martínez & Cano-Lozano, 2022c;Simmons et al, 2020). However, the occurrence of exposure to violence at home, as a risk factor, does not explain, on its own, how this leads an adolescent to behave in a violent manner with his/ her parents.…”
Section: The Role Of Direct Victimization At Home In Cpvmentioning
confidence: 99%
“…In the current study, almost 70% ( n = 523, 67%) of adolescents had been exposed to police reported parental IPV before age 13 years (with 28% ( n = 220) the victim of a family violence related verbal argument and 17% ( n = 135) the victim of a family violence assault offence prior to their first adolescent to parent violence offence). Across the body of adolescent to parent violence research evidence, exposure to violence at home (see reviews by Armstrong et al, 2018 and Simmons et al, 2018) and difficult family circumstances (Cuervo, 2021; Maroto & Cortés, 2018; Moulds, Mayshak, et al, 2019) are factors that are consistently related to adolescent to parent family violence. Higher rates of exposure to parental IPV and family violence related victimization have also been found amongst adolescent to parent violence offending groups when compared to adolescents involved in other types of offending (Contreras & Cano, 2015; Cuervo, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Across the body of adolescent to parent violence research evidence, exposure to violence at home (see reviews by Armstrong et al, 2018 and Simmons et al, 2018) and difficult family circumstances (Cuervo, 2021; Maroto & Cortés, 2018; Moulds, Mayshak, et al, 2019) are factors that are consistently related to adolescent to parent family violence. Higher rates of exposure to parental IPV and family violence related victimization have also been found amongst adolescent to parent violence offending groups when compared to adolescents involved in other types of offending (Contreras & Cano, 2015; Cuervo, 2021). The findings of the current study offer additional support for theoretical explanations suggesting an intergenerational association between children witnessing or experiencing family violence and then using violence against parents, other family members and in future intimate partner relationship (Harbin & Madden, 1979; Holt & Retford, 2013; Kaufman-Parks et al, 2018; Mahoney & Donnelly, 2000; Widom, 1989).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation